Synthesis, characterization, and computational evaluation of some synthesized xanthone derivatives: focus on kinase target network and biomedical properties - Muslim, Wisam Taher; Mohammad, Layth Jasim; Naji, Munaf M.; Karimi, Isaac; Al-Sabti, Matheel D.; Jabir, Majid; Najm, Mazin A. A.; Schiöth, Helgi B. (Frontiers in Pharmacology, 2025)
BackgroundXanthones are dubbed as putative lead-like molecules for cancer drug design and discovery. This study was aimed at the synthesis, characterization, and in silico target fishing of novel xanthone derivatives.MethodsThe products of reactions of xanthydrol with urea, thiourea, and thiosemicarbazide reacted with α-haloketones to prepare the thiazolone compounds. Xanthydrol reacted sequentially with ethyl chloroacetate, hydrazine, carbon disulfide, and α-haloketones to prepare the dithiolane. The xanthydrol reacted with propargyl bromide and it submitted to click reaction with azide to prepare triazole ring.ResultsFinally, four novel xanthones derivatives including (E)-2-(2-(9H-xanthen-9-yl)hydrazono)-1,3-dithiolan-4-one (L3), 2-(2-(9H-xanthen-9-yl)hydrazinyl)thiazol-5(4H)-one (L5), 2-(9H-xanthen-9-ylamino)thiazol-5(4H)-one (L7), and 4-((9H-xanthen-9-yloxy)methyl)-1-(4-nitrophenyl)-1H-1,2,3-triazole (L9) were synthesized and characterized using thin layer chromatography, Fourier-transform infrared spectroscopy, and nuclear magnetic resonance (1H and 13C). ADMET, Pfizer filter, adverse drug reaction, toxicity, antitarget interaction profiles, target fishing, kinase target screening, molecular docking validation, and protein and gene network analysis were computed for derivatives. Ligands obeyed Pfizer filter for drug-likeness, while all ligands were categorized as toxic chemicals. Major targets of all ligands were predicted to be kinases including Haspin, WEE2, and PIM3. Mitogen-activated protein kinase 1 was the hub gene of target kinase network of all derivatives. All the ligands were predicted to show hepatotoxic potentials, while L7 presented cardiac toxicity.ConclusionAcute leukemic T-cells were one of the top predicted tumor cell lines for these ligands. The possible antileukemic effects of synthesized xanthone derivatives are potentially very interesting and warrant further studies.